PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR SISWA MATEMATIKA SISWA KELAS III SEKOLAH DASAR - Aprimadedi; Marlianda, Rendi; Verliana, Verliana (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
The mathematics learning process in class III of Sitiung State Elementary School 20 has been found to lack interest and has not been effective in encouraging active student participation. The present situation has a deleterious effect on students' achievement in mathematics, which remains comparatively low. Consequently, there is a necessity for the implementation of effective and engaging learning methodologies to enhance mathematics learning outcomes. The objective of this study is to ascertain the extent to which the Teams Games Tournament (TGT) learning model exerts an influence on the mathematics learning outcomes of third grade elementary school students. This research employs an experimental study design, utilizing a true experimental research design, specifically a posttest-only control design. The research was conducted at State Elementary School 20 Sitiung, Sitiung District, Dharmasraya Regency. The research sample consisted of 49 students who were all third grade students. The data collection instrument employed was a multiple-choice test comprising 20 items, which had previously undergone rigorous validity and reliability testing. The findings indicated that the mean value of the experimental class posttest was 73.54, while the mean value of the control class posttest was 44. The research data from the posttest data analysis, utilizing the Independent Sample Test, yielded a significance value of 0.000 <0.05. Pursuant to the established criteria, when the significance is less than 0.05, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that the application of the Teams Games Tournament (TGT) learning model has a significant effect on the learning outcomes of third grade mathematics students at SDN 20 Sitiung.